Subsequence Sums of Zero-sum-free Sequences - Yuan, Pingzhi (The Electronic Journal of Combinatorics, 2009)
Let G be a finite abelian group, and let S be a sequence of elements in G. Let f(S) denote the number of elements in G which can be expressed as the sum over a nonempty subsequence of S. In this paper, we slightly improve some results of Pixton on f(S) and we show that for every zero-sum-free sequences S over G of length |S|=(G)+2 satisfying f(S)≥ 4(G)-1.